Method for preparing graphene by utilizing high-efficiency physical stripping of ultrahigh-pressure impinging stream

By using an ultra-high pressure impingement flow method to shear and impact graphite suspensions, combined with filtration and drying steps, the problems of low efficiency and uneven particle size in graphene preparation were solved, achieving efficient and uniform graphene preparation.

CN120964790APending Publication Date: 2025-11-18XIAN INT UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511480685.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-16
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing methods for preparing graphene suffer from low efficiency and uneven particle size distribution. Chemical vapor deposition is inefficient, redox methods produce poor quality, and mechanical pulverization results in uneven particle size distribution.

Method used

Graphene was prepared by pressurizing a graphite suspension to 250-300 MPa using an ultra-high pressure impingement flow method and ejecting it through multiple high-speed nozzles at an angle of 130°-155° to induce shear force, impact force, and cavitation effect. Combined with filtration and drying steps, graphene was then prepared.

Benefits of technology

This method improves the pulverization efficiency and particle size distribution uniformity of graphene, solving the problems of low efficiency and uneven particle size in traditional methods. The resulting graphene products meet the requirements of high-end applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120964790A_ABST
    Figure CN120964790A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing graphene by utilizing ultrahigh-pressure impinging stream high-efficiency physical exfoliation. The method comprises the following steps: crushing a raw material graphite block until the particle size is less than 100 microns; mixing the pretreated substance with a dispersing agent and a solvent to obtain a graphite suspension; pressurizing the graphite suspension to 250-300MPa, jetting the graphite suspension at a high speed from a nozzle arranged in an impact cavity, and performing collision to obtain a graphene mixed solution; the included angle between the axes of the spouts of the adjacent nozzles is 130-155 degrees; filtering the graphene mixed solution to obtain filter residues and filtrate containing graphene; and drying the filtrate to obtain a graphene product, so that 250-300MPa ultrahigh-pressure impinging stream is adopted to drive the graphite suspension, and shearing force, impact force, cavitation effect and turbulence effect are generated through high-speed jet flow spraying and collision of a nozzle, so that efficient dissociation between graphite layers is realized, and finally, the particle size of the graphene reaches D50lt. 2 [mu] m, D90lt; and the range is 5 microns. The crushing and stripping efficiency is improved through the synergistic effect of high pressure and angle, and the problems of low efficiency and non-uniform particle size distribution of a traditional method are solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of graphene preparation, and particularly relates to a method for preparing graphene by using high-efficiency physical exfoliation of super-high pressure impinging flow. BACKGROUND

[0002] As a two-dimensional material composed of single-layer carbon atoms, graphene has a broad application prospect in the fields of electronic devices, energy storage, biomedicine, etc. due to its excellent electrical conductivity, thermal conductivity, mechanical strength and flexibility. With the progress of science and technology, especially in the field of nanotechnology, the size accuracy and quality of graphene have become key factors affecting its performance, and higher requirements have been put forward for material preparation technology.

[0003] At present, the main preparation methods of graphene include chemical vapor deposition method, oxidation-reduction method and mechanical crushing method. The graphene prepared by the chemical vapor deposition method has high quality, but the equipment investment is large and the production efficiency is low; the oxidation-reduction method has low cost and is suitable for mass production, but the product quality is poor. The mechanical crushing method mainly separates the interlayer structure of graphite through physical force, which includes the following several ways: Ball milling method: mechanical shearing force is applied to graphite particles in a rotating or vibrating container by using hard milling balls to separate the interlayer structure of graphite and form graphene sheet. This method has a large processing capacity, but the collision force between the milling balls and the graphite particles is uneven, which easily leads to sheet tearing and secondary stacking, and the particle size distribution is wide.

[0004] Ultrasonic crushing method: single-layer or few-layer graphene is obtained by crushing the interlayer structure of graphite through the cavitation effect and shearing force generated by high-frequency ultrasonic waves in liquid. This method is suitable for small-scale laboratory preparation, but the ultrasonic energy decays exponentially in liquid, resulting in uneven distribution of action force in space and time, and it is difficult to accurately control the sheet size.

[0005] In summary, the existing mechanical crushing method can better maintain the structure of graphene, but it has the problems of low efficiency and uneven particle size distribution.

[0006] Therefore, there is an urgent need for a solution to solve the problems in the prior art. SUMMARY

[0007] The main purpose of the present application is to provide a method for preparing graphene by using high-efficiency physical exfoliation of super-high pressure impinging flow, to at least solve the problems of low production efficiency of graphene by chemical vapor deposition method, poor quality of graphene by oxidation-reduction method, and low efficiency and uneven particle size distribution of mechanical crushing method in the prior art.

[0008] In order to achieve the above purpose, the present application provides a method for preparing graphene by using high-efficiency physical exfoliation of super-high pressure impinging flow, comprising the following steps: crushing raw material graphite blocks to a particle size of less than 100 μm to obtain a pretreatment product; mixing the pretreatment product with a dispersant and a solvent to obtain a graphite suspension; pressurizing the graphite suspension to 250-300 MPa, and jetting the graphite suspension from multiple nozzles arranged in a collision chamber to obtain a graphene mixture; the angle between the nozzle axes of adjacent nozzles is 130-155°, the nozzle distance of adjacent nozzles is 1.8-2.2 cm, and the inner diameter of the inner wall of the collision chamber is 15-20 cm; filtering the graphene mixture to obtain a filter residue and a graphene-containing filtrate; drying the filtrate to obtain a graphene product.

[0009] Optionally, the solvent is one of water, ethanol, and liquid carbon dioxide.

[0010] Optionally, before mixing the pretreatment product with the dispersant and the solvent, the method further comprises: performing microwave expansion treatment on the pretreatment product.

[0011] Optionally, the concentration of the graphite suspension is 1-5 wt%.

[0012] Optionally, when the graphite suspension is pressurized to 250-300 MPa, a high-pressure plunger pump is used as the pressurizing device.

[0013] Optionally, after obtaining the graphene mixture, the method further comprises: monitoring the values of the graphene particle sizes D50 and D90 in the graphene mixture: if D50 < 2 μm and D90 < 5 μm, performing filtration treatment on the graphene mixture; if D50 > 2 μm or D90 > 5 μm, continuing to jet the graphene mixture from the nozzles to perform high-speed jet collision.

[0014] Optionally, when the graphene mixture is filtered, a centrifuge or a filter plate machine is used.

[0015] Optionally, after obtaining the filter residue and the graphene-containing filtrate, the method further comprises: continuing to add the filter residue to the graphite suspension.

[0016] Optionally, after obtaining the graphene mixture, the method further comprises: returning the graphene mixture to the graphite suspension, and repeating the process 3-8 times.

[0017] Optionally, the drying treatment uses one of spray drying, supercritical drying, and microwave vacuum drying.

[0018] The technical scheme of the present application is a method for preparing graphene by using high-pressure impinging stream high-efficiency physical stripping, comprising the following steps: crushing raw material graphite blocks to a particle size of less than 100 μm to obtain pretreated material; mixing the pretreated material with a dispersing agent and a solvent to obtain a graphite suspension; pressurizing the graphite suspension to 250-300 MPa, and jetting high-speed jets from multiple nozzles arranged in an impinging chamber to obtain a graphene mixture; in the multiple nozzles, the included angle of the jet axes of adjacent nozzles is 130-155°, the jet distance of adjacent nozzles is 1.8-2.2 cm, and the inner diameter of the impinging chamber is 15-20 cm; filtering the graphene mixture to obtain filter residue and a filtrate containing graphene; and drying the filtrate to obtain a graphene product, so that the graphite suspension is driven by the 250-300 MPa high-pressure impinging stream, the high-speed jets from the nozzles with an included angle of 130-155° are jetted to collide to generate shear force, impact force, cavitation effect and turbulent flow, the graphite layers are efficiently dissociated, and finally the particle size of the graphene is in the range of D50<2 μm and D90<5 μm. The crushing and stripping efficiency is improved by the synergistic effect of high pressure and angle, and the problems of low efficiency and uneven particle size distribution in the traditional method are solved. BRIEF DESCRIPTION OF DRAWINGS

[0019] The drawings accompanying the specification of this application form a part thereof, serve to provide further understanding of the application, and together with the description of the exemplary embodiments of the application and the explanation thereof, make an explanation of the application complete, and do not constitute an improper limitation of the application. In the drawings: Figure 1 is an optional method flow chart for preparing graphene by using high-pressure impinging stream high-efficiency physical stripping according to an embodiment of the present application; Figure 2 is an optional system diagram for preparing graphene by using high-pressure impinging stream according to an embodiment of the present application. DETAILED DESCRIPTION

[0020] It should be noted that the embodiments and the features in the embodiments in the present application can be combined with each other without conflict. The present application will be described in detail below with reference to the drawings and in combination with the embodiments.

[0021] As shown in Figure 1 , the present application provides a method for preparing graphene by using high-pressure impinging stream high-efficiency physical stripping, comprising the following steps: S1, crushing raw material graphite blocks to a particle size of less than 100 μm to obtain pretreated material; S2, mixing the pretreated material with a dispersing agent and a solvent to obtain a graphite suspension; S3, pressurize the graphite suspension to 250-300 MPa, and jet out the counter-impingement from multiple nozzles arranged in the impingement chamber at high speed to obtain a graphene mixture; in the multiple nozzles, the included angle between the jet axes of adjacent nozzles is 130-155°, the jet distance between adjacent nozzles is 1.8-2.2 cm, and the inner diameter of the inner container in the impingement chamber is 15-20 cm; S4, filter the graphene mixture to obtain filter residue and a filtrate containing graphene; S5, dry the filtrate to obtain a graphene product.

[0022] Specifically, S1, the blocky graphite raw material is treated by mechanical pulverization (such as ball milling, air flow pulverization) to control the particle size to be less than 100 microns to form a uniform pretreatment product. This step increases the specific surface area by reducing the macroscopic size of the graphite particles, providing more active sites for subsequent high-pressure pulverization, while avoiding blockage of subsequent equipment by large particles. The ball mill is used to pulverize the raw material graphite block in the present application, and the specific process parameters are as follows: ball-to-material ratio of 10 to 1 to 20 to 1, ball milling time of 2 to 4 hours, rotation speed of 200 to 400 revolutions per minute, and inert gas protection to prevent graphite oxidation. At the same time, 0.1 to 1 weight percent of a dispersant is added to assist dispersion and prevent particle agglomeration, and finally a pretreated graphite powder with uniform particle size distribution is obtained.

[0023] S2, mix the pretreated graphite particles with a dispersant and a solvent to prepare a stable suspension. The dispersant can be adsorbed on the surface of the graphite particles to reduce the tendency of particle agglomeration; the solvent provides suitable fluidity to ensure uniform delivery of the suspension in the high-pressure system. The dispersant is selected from amphiphilic dispersants such as PVP and SDS. The hydrophilic groups in the molecular structure of the dispersant combine with the solvent, and the hydrophobic groups adsorb on the surface of the graphite to form a protective layer of 1-2 nm thick. The viscosity of the suspension is controlled within a suitable range to ensure fluidity and prevent particle settling. Ultrasonic assisted dispersion is used to effectively destroy the soft agglomeration of graphite particles, and the dispersant molecules uniformly coat the surface of the particles. The ultrasonic conditions are 20-40 kHz and 10-30 min.

[0024] S3, the graphite suspension is pressurized to 250-300 MPa and sprayed out through multiple nozzles at high speed, the included angle between the jet axes of adjacent nozzles is 130-155° and the nozzle distance is 1.8-2.2 cm; the distance and the included angle work together to make the impinging streams accurately impinge in a specific area of the impingement chamber, avoiding both insufficient energy release before dissipation due to too close distance and energy density drop in the core collision area due to too far distance, maximizing the excitation of shear force, impact force, cavitation effect and turbulent flow. The instantaneous pressure peak of the high-pressure impinging streams can reach 5-8 times of the initial pressure, and the nozzle distance of 1.8-2.2 cm further ensures that the pressure peak acts stably on the interlayer of graphite particles, efficiently overcoming the van der Waals force between the layers to drive the graphite to be crushed layer by layer into thin-layer graphene, while also reducing the impact force of the rebounding impinging streams on the nozzles to reduce wear and tear and prolong the service life of the equipment, and make the flow field in the impingement chamber more stable and reduce local turbulent flow disturbance, improving the crushing and exfoliation efficiency while ensuring more uniform size distribution of graphene sheets and reducing the problem of excessive crushing or insufficient crushing. A ceramic liner is arranged in the impingement chamber, and the inner diameter of the ceramic liner is 15-20 cm. The ceramic liner can resist the instantaneous impact of the 250-300 MPa high-pressure impinging streams and the scouring of graphite particles due to its high hardness and chemical stability, avoiding wear and tear of the metal substrate of the impingement chamber and preventing metal impurities from contaminating the graphene; and the 15-20 cm inner diameter design keeps the space in the chamber moderately compact, avoiding rapid dissipation of the fluid energy after impingement due to excessive space, and allowing the high-speed fluid to form a short-distance secondary impingement or turbulent disturbance in the chamber, further strengthening the shear force and impact effect and helping the graphite to be fully exfoliated into thin-layer graphene.

[0025] S4, the graphene mixture is separated by filtration, and the graphite particles that are not fully crushed (particle size >5 μm) are retained as filter residue, and the filtrate (containing graphene with D50<2 μm and D90<5 μm) is collected. The separation process is based on the size difference of the particles: thin-layer graphene can pass through the pores of the filter material smoothly due to its two-dimensional sheet structure (thickness only nanoscale) and small lateral size (1-5 μm); while large particles that are not crushed are retained due to their large volume, achieving effective enrichment of the target product.

[0026] S5, the separated filtrate is dried to obtain a solid graphene product after removing the solvent. The drying process needs to control the temperature, pressure and atmosphere conditions to remove the residual solvent while avoiding the re-stacking of graphene sheets. The final product maintains a few-layer structure (number of layers <10), high specific surface area and excellent electrical conductivity, meeting the quality requirements of graphene for high-end applications.

[0027] The jet axis angle between the plurality of nozzles can be adjusted as needed, and the collision mode and energy distribution of the high-pressure impinging flow can be regulated by changing the included angle of the jet axis of the nozzles, and the adjustment range is 130° to 155°. The included angle range of 130° to 155° of the jet axis provides an optimal angle interval for the preparation of graphene by the super-high-pressure impinging flow, which has high efficiency of peeling, structure protection and stable production: any included angle in this range can ensure that the high-pressure jet collision forms sufficient shear force, impact force and cavitation effect, effectively destroys the interlayer force of graphite to achieve peeling, avoids excessive dispersion of energy in the collision area due to too small included angle (such as <130°) to achieve sufficient crushing and peeling effect, and prevents excessive concentration of energy due to too large included angle (such as >155°) to damage the conjugated structure of graphene; at the same time, the included angle in this interval can make the impinging flow form a uniform energy distribution in the impinging chamber, reduce coarse particles that are not fully peeled and impurities that are excessively crushed, improve the particle size uniformity of the graphene product, and also slow down the direct impact of the super-high-pressure jet on the nozzle, reduce equipment wear, adapt to super-high-pressure working conditions of 250~300MPa, and ensure the stability and continuity of the entire preparation process. The nozzle overcurrent channel is embedded with sapphire (single crystal alpha-Al2O3), or is made of sapphire (single crystal alpha-Al2O3) as a whole.

[0028] In addition, an annular jacket is arranged outside the impinging chamber, which is completely matched with the shape of the outer wall surface of the impinging chamber, and a heat transfer medium flows inside to form a closed cycle. During operation, low-temperature heat transfer medium (such as cooling water or low-temperature heat conducting oil) at 5~8℃ is first introduced into the annular jacket to directly absorb the heat generated during the super-high-pressure collision process in the impinging chamber, rapidly reduce the internal temperature of the impinging chamber, and avoid local overheating affecting the peeling effect of graphene or causing damage to the equipment.

[0029] The present application drives the graphite suspension by 250~300MPa super-high-pressure impinging flow, and the graphite is finally peeled off by the shear force, impact force, cavitation effect and turbulent flow generated by the high-speed jet of the nozzle with an included angle of 130°~155°, so that the particle size of the graphene reaches D50<2μm and D90<5μm. The crushing efficiency is improved by the synergistic effect of high pressure and angle, and the problems of low efficiency and uneven particle size distribution in the traditional method are solved.

[0030] In one possible implementation, the solvent is one of water, ethanol and liquid carbon dioxide.

[0031] Specifically, water has significant advantages as the preferred solvent, with moderate surface tension (0.072 N / m) and high dielectric constant (78.5), which can effectively wet the graphite surface and stably disperse the particles, and is widely available, low in cost and environmentally friendly; when it is necessary to adjust the polarity of the system or improve the dispersion performance in specific application scenarios, ethanol can be used as a substitute solvent, which has a low boiling point (78.3°C) and is conducive to the rapid implementation of subsequent drying processes, and the mutual solubility of ethanol and water facilitates the optimization of process parameters by adjusting the mixing ratio. Both solvents do not chemically react with graphite, can maintain the integrity of the intrinsic structure of graphene, and are easy to recycle and reuse through simple distillation. In addition, liquid carbon dioxide can also be used as a solvent, which is easy to recover and can be separated by direct vaporization under reduced pressure at the end of the process without complex recovery steps such as distillation, which can minimize the pollution of the graphene surface by the solvent.

[0032] In a possible implementation, before mixing the pretreated material with the dispersant and the solvent, the method further includes: performing microwave expansion treatment on the pretreated material.

[0033] Specifically, before mixing the pretreated material with the dispersant and the solvent, microwave expansion treatment is performed on the pretreated graphite particles. The pretreated graphite particles with a particle size of less than 100 μm are placed in a microwave reaction cavity and irradiated at a frequency of 2450 MHz and a power of 800-1500 W for 30-60 seconds. Through the microwave heat effect, the intercalation compounds (such as sulfate, oxide, etc.) in the graphite layers are instantaneously decomposed to produce CO2, SO2 and other gases. These gases rapidly accumulate between the layers to form a thrust, which expands the interlayer distance of the graphite from the original 0.335 nm to 1.0-1.1 nm, and at the same time, the overall volume of the graphite particles is significantly expanded (with an expansion rate of 300-500 times) to form a loose and porous vermicular structure. The microwave reaction cavity is filled with nitrogen during the process to avoid excessive oxidation. The expanded graphite after treatment has an expanded interlayer distance, and the interlayer binding energy is significantly reduced, so that the energy required for subsequent crushing is reduced; its specific surface area is increased from 10-20 m 2 / g before pretreatment to 300-500 m 2 / g, providing more active sites for high-pressure impinging flow. At the same time, the selective heating characteristics of the microwave make the inside and outside of the particles uniformly heated, avoiding the local structural defects easily produced by traditional thermal expansion, and finally forming expanded graphite raw materials with uniform thickness and stable lateral size, which can significantly improve the yield and quality consistency of graphene.

[0034] In a possible implementation, the concentration of the graphite suspension is 1-5 wt%.

[0035] Specifically, when the concentration is lower than 1wt%, the number of effective graphite particles in unit volume is insufficient, resulting in a decrease in the utilization rate of high-pressure impinging stream energy and a significant decrease in the crushing yield, and at the same time, the solvent consumption is greatly increased to achieve the same processing capacity, causing an increase in the load of subsequent separation and purification and the production cost; if the concentration exceeds 5wt%, the viscosity of the suspension increases sharply, which not only affects the stable delivery of the high-pressure pump, but also easily causes nozzle blockage, and under high concentration conditions, the interaction between particles is enhanced, which easily forms secondary agglomerates, weakens the shearing effect of the impinging stream, and results in an increase in the defects of the graphene sheet structure. By precisely controlling the concentration parameter, sufficient graphite particles can be ensured to participate in the crushing reaction per unit time, and the flowability and dispersion stability of the suspension can be maintained, ensuring the efficient operation of the high-pressure impinging stream system.

[0036] In one possible implementation, when the graphite suspension is pressurized to 250-300MPa, the pressurizing device used is a high-pressure plunger pump.

[0037] Specifically, the high-pressure plunger pump generates a stable pressure of 250-300MPa through a multi-stage pressurization structure, and the high-strength alloy pump head and wear-resistant sealing assembly can ensure no leakage during long-time high-pressure operation. The pump body is driven by a variable frequency motor to realize stepless adjustment of the flow rate. The pressure regulating module integrates a high-precision PID controller and an electric servo actuator, and a high-pressure regulating valve is arranged between the outlet pipeline of the high-pressure plunger pump and the inlet of the nozzle. The high-pressure regulating valve is made of 316L stainless steel and has a pressure resistance level of 400MPa. The high-pressure regulating valve and the PID controller form a closed-loop control circuit. By monitoring the feedback signal of the impinging stream pipeline pressure sensor in real time, the accuracy is ±0.5MPa, and the valve opening is dynamically adjusted to stabilize the pressure fluctuation within ±1.5MPa, which meets the crushing energy level requirements of graphite of different particle sizes.

[0038] In one possible implementation, after obtaining the graphene mixture, the following steps are further included: Monitoring the values of the graphene particle sizes D50 and D90 in the graphene mixture: if D50<2μm and D90<5μm, filtering the graphene mixture; If D50>2μm or D90>5μm, the graphene mixture is continuously sprayed out by the high-speed jet of the nozzle for impingement.

[0039] Specifically, the particle size of graphene is detected by a laser diffraction particle size analyzer. The laser diffraction particle size analyzer mainly comprises a laser emitter, a multi-element detector array, a sample circulating pool and a data processing unit. A semiconductor laser with a wavelength of 635 nm is used to generate a parallel light beam, which is used to irradiate the graphene suspension flowing through the measuring pool. Different particle sizes cause the laser to produce scattering at a specific angle. The multi-element detector captures the scattering light intensity distribution. The particle size distribution is calculated by Mie scattering theory. The laser diffraction particle size analyzer has a measurement range of 0.01-3000 μm, a sampling frequency of ≥1 time / minute, a resolution of 0.1 μm, and an IP65 protection level to adapt to high-pressure environment and stable operation.

[0040] After obtaining the filter residue and the filtrate containing graphene, the system detects the particle size distribution of graphene in the mixed solution in real time through an online particle size monitor. The monitor is installed on the conveying pipeline between the outlet of the ultra-high pressure impinging stream reactor and the filtering device. The high-pressure seal is ensured by flange connection (PN25 pressure rating). The built-in automatic backflushing device prevents particle deposition. When the monitoring data shows that D50 is less than 2 μm and D90 is less than 5 μm, it indicates that the graphene has reached the target particle size requirement. At this time, the system directs the mixed solution into the filtering device for filtering, and the finished product is obtained after drying. If D50 is greater than 2 μm or D90 is greater than 5 μm, it indicates that the graphene crushing is not complete. After the system starts the backflow program, the backflow pump will extract the substandard mixed solution from the temporary storage (such as the intermediate liquid storage tank) and transport it through the high-pressure resistant backflow pipeline (made of 316L stainless steel that can withstand high pressure). The backflow pipeline and the normal liquid supply path directly converge in the area before entering the nozzle, so that the backflow mixed solution and the normal mixed solution are fully mixed before entering the nozzle. Then, they are sprayed together in a high-pressure state through the nozzle, and collide with each other in the impingement chamber. Through this high-pressure impinging stream effect again, the graphene is further refined.

[0041] In one possible implementation, when the graphene mixed solution is filtered, a centrifuge or a filter plate machine is used.

[0042] Specifically, if the scale production is more than 100 kg per day, a horizontal screw sedimentation centrifuge is preferred. The high speed of 3000-5000 r / min can realize strong centrifugal force separation, the single separation time is less than 5 minutes, and the device can work continuously for 24 hours. It is suitable for the high-efficiency preparation rhythm of ultra-high pressure impinging stream, and can be automatically operated with the particle size monitoring system, greatly reducing the labor cost. If small batch production or high purity graphene such as electronic grade is needed, a filter plate machine is preferred. The retention rate of the filter cloth with a pore size of 1-3 μm is more than 98%, which can accurately filter out coarse particles. The equipment procurement and maintenance cost is only 1 / 3-1 / 2 of the centrifuge with the same processing capacity. The operation is simple and more suitable for small batch refining requirements. The filter residues separated by the two devices can be returned to the graphene suspension for secondary crushing, ensuring that the raw material utilization rate is more than 95%.

[0043] In a possible implementation, after obtaining the filter residue and the filtrate containing graphene, the method further comprises: continuously adding the filter residue into the graphite suspension.

[0044] Specifically, after obtaining the filter residue and the filtrate containing graphene, the filter residue is continuously added into the graphite suspension to form a closed-loop system. The uncompletely crushed graphite particles are re-dispersed in the suspension by high-speed stirring and re-enter the high-pressure impinging stream collision zone for secondary crushing. The filter residue is recycled and gradually crushed by multiple moderate shearing, impinging, cavitation and turbulent flow, etc., which not only avoids the damage of graphene structure caused by single high-pressure crushing, but also significantly improves the utilization rate of graphite raw materials, reduces the discharge amount of filter residue, and meets the requirements of green manufacturing.

[0045] In a possible implementation, after obtaining the graphene mixture, the method further comprises: returning the graphene mixture into the graphite suspension, and repeating 3 to 8 times.

[0046] Specifically, when the particle size of graphene in the graphene mixture does not meet the target requirement, i.e., D50>2 μm or D90>5 μm, the graphene mixture is subjected to high-pressure impinging crushing again, and the cycle is repeated 3 to 8 times. If the cycle is less than 3 times, the crushing effect of the high-pressure impinging stream on the graphite is insufficient, and it is difficult to meet the target particle size requirement. If the cycle is more than 8 times, the marginal benefit is significantly reduced, and the graphene sheet layer is prone to structural defects due to repeated shearing. In addition, the suspension needs to be maintained at a suitable concentration each time. If the concentration is too high, the van der Waals force between particles is enhanced, and secondary agglomerates are easily formed, which reduces the crushing efficiency. If the concentration is too low, the unit volume production capacity is reduced, and frequent replenishment affects continuous production. In addition, the pH value is adjusted in real time (maintained at pH=9-10) during the cycle process, which can effectively inhibit the re-agglomeration phenomenon caused by the neutralization of the surface charge of the graphite.

[0047] In a possible implementation, the drying process adopts one of spray drying, supercritical drying and microwave vacuum drying.

[0048] Specifically, in this application, one of spray drying, supercritical drying and microwave vacuum drying can be used for drying the filtrate. Among them, the spray drying method atomizes the graphene filtrate into fine droplets through a high-pressure nozzle, contacts with hot air in the drying tower, and the water is rapidly evaporated to form a powder. This method is suitable for continuous large-scale production, can quickly complete the dehydration process, is simple to operate and has high processing efficiency, and is suitable for high-efficiency drying demand on industrial production line; the supercritical drying method utilizes the special properties of supercritical fluid to convert the water in graphene into gaseous state for removal under supercritical state. This technology can gently remove water, effectively maintain the nanometer structure integrity of graphene, and is particularly suitable for application scenarios with high requirements for structure integrity, ensuring that the product has excellent physical and chemical properties. The microwave vacuum drying method directly acts on water molecules through microwave in a vacuum environment to achieve rapid and uniform dehydration. This method has high heating efficiency and can complete the drying process at a lower temperature, effectively reducing the influence of thermal stress on the graphene sheet structure, and is suitable for drying treatment of graphene products with high thermal sensitivity, ensuring product quality.

[0049] The spray drying method is preferably used in this application, and the specific operation process is as follows: First, the graphene filtrate after centrifugal filtration is delivered to a centrifugal atomizer through a high-precision screw pump, and the pumping pressure is maintained in the range of 0.3 to 0.6 MPa to ensure uniform droplet size. The atomizer rotates at high speed to disperse the filtrate into fine droplets with a diameter of 50 to 150 microns, forming a uniform mist cone that is sprayed into the drying tower. At the same time, hot air heated to 180 to 220°C by a hot air furnace enters from the bottom tangentially and contacts the mist droplets in counterflow, with a hot air flow rate of 3 to 5 meters per second to form a stable vortex flow field. The droplets rapidly evaporate water in a suspended state in the tower, and the drying time is controlled to be completed within 3 to 5 seconds. The formed graphene powder rises with the airflow to the top of the tower, and the gas-solid separation is carried out by a cyclone separator. The finished powder falls into the bottom collection tank, and the tail gas is removed by a bag dust collector after removing a small amount of dust, and then exhausted by an induced draft fan. The three core parameters of feed flow, inlet air temperature and tower negative pressure are monitored in real time during the whole process. The feed flow is adjusted by a variable frequency pump to match the evaporation capacity. A large temperature deviation will cause local overheating or adhesion, and an unbalanced negative pressure may cause powder escape or accumulation. The water content of the dried powder can be reduced to below 0.5wt%, and the bulk density is 0.05 to 0.15g / cm 3 , which meets the subsequent processing requirements.

[0050] The specific process of the method for preparing graphene by using ultra-high pressure impinging stream high-efficiency physical peeling is as follows: Firstly, the blocky graphite raw material is put into a ball mill for mechanical crushing. In a nitrogen protection environment, the ball-to-material ratio is set to 15:1 (the ball milling medium is a stainless steel ball with a diameter of 5-10 mm), and the rotation speed is set to 300 revolutions per minute for 3 hours. The graphite particle size is reduced to a pretreatment state of D50=50 microns and D90=80 microns. This process increases the specific surface area to improve the subsequent crushing efficiency, while avoiding the blockage of high-pressure pipelines by large particles. Subsequently, the pretreated graphite is transferred to a microwave reaction cavity. Under the conditions of a microwave frequency of 2450 MHz and a power of 1200 W, the graphite is irradiated for 45 seconds. High-purity nitrogen gas is filled into the cavity to prevent oxidation, so that the intercalation compound of the graphite layer is decomposed to generate gas, the interlayer spacing of the graphite layer is expanded from the original 0.335 nm to 5 nm, and a fluffy and porous expanded graphite structure is formed. The specific surface area of the expanded graphite is increased from 15 m 2 / g of the pretreatment to 400 m 2 / g, providing more active sites for high-pressure crushing.

[0051] The expanded graphite after microwave treatment is mixed with a dispersant and a solvent to prepare a suspension. The dispersant is PVP (polyvinylpyrrolidone) with a molecular weight of 40000, and the addition amount is 0.5wt% of the mass of the graphite. The solvent is deionized water. The mixture is added to a stirred tank with a jacketed cooling, and a 25 kHz ultrasonic generator is turned on for 20 minutes. The ultrasonic power is set to 300 W, so that the PVP molecules form a 1.5 nm thick protective layer on the surface of the graphite. At the same time, mechanical stirring is used to maintain the uniformity of the suspension. The concentration of the suspension is controlled to be 3wt%, and at this time the viscosity of the system is 800 mPa·s, which ensures the stability of the high-pressure pump delivery and avoids the risk of nozzle blockage.

[0052] The prepared suspension is delivered to a high-pressure plunger pump through a high-precision screw pump. The pump head is made of tungsten-cobalt hard alloy material with a pressure rating of 400 MPa. After starting the pump body, the suspension is pressurized to 200 MPa (the target pressure is set by a PID controller, and the built-in pressure sensor provides real-time feedback with a fluctuation range of ±1.5 MPa). The high-pressure fluid is delivered to the impingement chamber through the heat preservation pipeline. The nozzles of adjacent nozzles are arranged at an angle of 135° relative to each other. The nozzle diameter is 0.2 mm, and the material is zirconia ceramic. The impinging flow generates a transient pressure peak of 1600 MPa (8 times the initial pressure) in the collision area, forming a high-energy density region between the graphite particle layers, so that the van der Waals force between the graphite layers is destroyed, and the graphite is gradually crushed into thin-layer graphene. During this process, the temperature of the suspension increases to 135°C due to high-pressure shearing, and is maintained below 80°C by circulating cooling water to prevent damage to the graphene structure caused by high temperature.

[0053] The mixed solution after crushing enters an online particle size monitoring system, which is composed of a laser emitter (wavelength 635 nm), a multi-element detector array and a data processing unit. The material of the measuring pool is 316L stainless steel with a pressure rating of PN25. The suspension passes through the measuring pool at a flow rate of 10 mL / min. The scattered light generated by laser irradiation is captured by 48 detectors. The particle size distribution is calculated in real time by Mie scattering theory. The data stream of the online particle size monitor is collected in real time by a PLC control system to continuously monitor the particle size distribution of graphene. When the detection data shows that the D50 and D90 values are within the target range, the system automatically determines that it is in a qualified state, triggers the valve switching command, and directs the mixed solution into the filtration device. Otherwise, if the target particle size values are not reached, the automatic backflow program is started to pump the mixed solution back into the graphite suspension storage tank. The circulation of pumping the mixed solution back into the graphite suspension storage tank is executed a maximum of 8 times.

[0054] The qualified mixed solution enters a two-stage filtration system. First, it passes through a horizontal centrifuge for primary separation. The rotor diameter is 600 mm, and the rotation speed is set to 10,000 rpm. Under the action of the centrifugal force field, graphite particles with a particle size greater than 5 μm that have not been crushed quickly settle on the inner wall of the drum and are discharged for collection by a screw conveyor. This process can remove about 80% of the large particle impurities in the mixed solution. The centrifuge has a processing capacity of 50 L / h and an energy consumption of 2 kW. Subsequently, the filtrate enters a plate and frame filter press, which uses an alumina ceramic filter plate with a pore size of 8 μm to trap residual micron-sized particles under a filtration pressure of 0.3 MPa. The permeate is a graphene filtrate with a D50 of less than 2 μm and a D90 of less than 5 μm. The two-stage filtration system reduces the solid content of the filter residue to 40 wt%, thereby reducing the amount of subsequent drying treatment.

[0055] The filter residue produced by filtration is transferred to a high-speed stirring tank, where it is dispersed with an appropriate amount of fresh suspension at a speed of 500 rpm for 15 minutes to re-suspend the uncrushed graphite particles. The suspension is then re-introduced into the high-pressure impinging stream system for secondary crushing. In addition, water is added to ensure that the concentration of the suspension meets the required specifications. This closed-loop circulation process increases the utilization rate of graphite raw materials to 92%, reducing the amount of filter residue discharged by 65% compared to traditional single-crushing processes.

[0056] The final graphene filtrate is subjected to dehydration treatment in a spray drying tower. A centrifugal atomizer is used to disperse the filtrate into droplets with a diameter of 80 microns. The atomizer rotates at a speed of 28,000 rpm, and the pumping pressure is 0.4 MPa. A hot air furnace generates hot air at 190°C, which enters the tower tangentially from the bottom and contacts the droplets in a counterflow. The hot air flows at a speed of 4 m / s, forming a stable vortex flow field. The droplets rapidly evaporate the water in the suspension state inside the tower, with a drying time of about 4 seconds. The formed graphene powder is collected by a cyclone separator, and the tail gas is purified by a bag filter before being discharged. The entire drying process controls the feed flow rate to be 20 L / h, the negative pressure in the tower is -8 Pa, the water content of the finished product is 0.3 wt%, and the bulk density is 0.1 g / cm 3The graphene sheet layer structure is ensured to be complete and oxidation caused by local overheating is avoided (oxygen content in the finished product < 1 wt%) by real-time monitoring of feed flow fluctuation (accuracy ± 0.5 L / h), air inlet temperature deviation (± 2 ℃), and stability of negative pressure in the tower (fluctuation < ± 1 Pa).

[0057] The graphene product produced in the embodiment is observed by transmission electron microscopy to have a sheet thickness of 3-8 nm (corresponding to 2-5 layers), a BET specific surface area of 750 m 2 / g, and an electrical conductivity of 10 5 S / m, meeting the application requirements of high-performance composite materials and energy storage devices. The entire process consumes 1.2 m 3 / t product of water and 800 kW·h / t of energy, which is reduced by more than 60% compared with the traditional Hummers method.

[0058] The application is further illustrated by the following experiments.

[0059] Comparative Example 1 An impinging stream reactor with a fixed angle of 90° between the axes of adjacent nozzles is used, the graphite raw material is 80 μm flake graphite, the suspension concentration is 3 wt%, and the high-pressure pump is set to a pressure of 280 MPa. The graphite suspension is crushed by the collision of the nozzles (angle of 90°) arranged opposite to each other after being pressurized by the pump, the temperature of the reactor is maintained below 40 ℃ (circulating water cooling of the jacket), and the graphene product is collected after the crushed mixture is centrifuged and filtered. The particle size distribution and structural defects are detected after 5 cycles of crushing. Example

[0060] Except that the angle between the axes of adjacent nozzles is adjusted to 130°, the other parameters are completely consistent with those of Comparative Example 1. This angle design significantly improves the concentration of the impinging stream collision area, and the impinging stream impact force is enhanced, which can produce higher local shear strength under the same pressure, and is particularly suitable for efficient crushing of conventional hardness graphite raw materials. The crushing cycle number and detection method are consistent with the foregoing experiment.

[0061] Example 2 The other parameters are kept the same as those of Comparative Example 1, and only the angle between the axes of adjacent nozzles is increased to 135°. This setting further optimizes the balance between the concentration and diffusion range of the impinging stream kinetic energy, so that the graphene crushing efficiency and structural integrity are simultaneously improved.

[0062] Example 3 The other parameters are kept the same as those of Comparative Example 1, and only the angle between the axes of adjacent nozzles is increased to 150°. This setting expands the diffusion range of the impinging stream, reduces the local shear strength, but improves the uniformity of energy distribution, is suitable for processing of high-hardness graphite raw materials, and significantly enhances the cycle stability. Example

[0063] Further increase the angle between the axes of the adjacent nozzles to 155°, which is the upper limit of the process design, based on Embodiment 3. The impinging flow collision area reaches the maximum diffusion state, and the pressure loss increases by about 15% compared to 150°. Embodiment

[0064] Continue to increase the angle between the axes of the adjacent nozzles to 160°, based on Embodiment 4. The impinging flow collision area is further expanded, and the pressure loss increases to a significant level (25% increase compared to 150°). Although the D90 can be reduced to 3.5 μm, the energy consumption rises by 80 kW·h / t, the overall benefit decreases, and the rationality of the upper limit of the angle is verified.

[0065] The comparative experimental data of the graphene crushing effect under different nozzle angle conditions are shown in Table 1.

[0066] Table 1 Comparative experimental data of the graphene crushing effect under different nozzle angle conditions

[0067] As can be seen from Table 1, when the angle is increased from 90° to 135°, the graphene particle size 130° distribution is significantly improved (D50 is reduced from 2.8 μm to 1.9 μm, and D90 is reduced from 6.5 μm to 4.3 μm), the defect density is reduced from 0.45 to 0.25, and the energy consumption reduction is reduced from 1250 to 980 kW·h / t, indicating that moderately increasing the angle can improve the shearing efficiency. The improvement of D50 / D90 under 130° angle is greater than the increase of energy consumption. Although the energy consumption under 155° angle is slightly higher than that under 150°, the D90 is further reduced to 3.6 μm, and the defect density reaches the lowest value of 0.18. When the angle exceeds 160°, the pressure loss leads to poor energy efficiency.

[0068] To further quantify the high efficiency of the method of the present application, the traditional physical exfoliation method (ultrasonic exfoliation method, mechanical exfoliation method) and the chemical exfoliation method (Hummers method) are selected as the control, and the same batch of 80 μm flake graphite is used as the raw material (total input amount 100 g). The optimal nozzle angle of 150° is used, and comparative experiments are carried out from three core dimensions of yield, preparation rate and graphene concentration. The specific data and analysis are as follows: (1) Yield comparison Table 2 Comparative experimental data of graphene yield of different preparation methods

[0069] As can be seen from Table 2, the qualified graphene yield of the method of the present application is 91.5% after only 1.5 h of treatment, and the unexfoliated residual rate is only 6.8%, and the filter residue can be recycled for secondary use; while the traditional physical method needs 24 h of treatment, and the yield is still less than 35%. Although the typical chemical method has a higher yield, the treatment time is more than 5 times that of the present application, and there is a problem of product loss.

[0070] (2) Preparation rate comparison Table 3. Comparison of graphene preparation rate of different preparation methods

[0071] As shown in Table 3, the preparation rate of qualified graphene by the method of the present application is 60.2 g / h, which is 44 times that of the ultrasonic exfoliation method, 54 times that of the mechanical exfoliation method, and 6.2 times that of the typical chemical method. At the same time, it can be continuously operated for 72 hours without failure, and the unit energy consumption output is 0.073 g / (kW·h), which is much higher than that of traditional methods, embodying the dual advantages of high efficiency and energy saving.

[0072] (Three) Comparison of graphene concentration Table 4. Comparison of graphene concentration and dispersion stability of different preparation methods

[0073] As shown in Table 4, the concentration of qualified graphene in the filtrate by the method of the present application is 8.5 mg / mL, which is 4 times that of the ultrasonic exfoliation method and 4.7 times that of the mechanical exfoliation method, and the sedimentation rate after standing for 24 hours is only 8.2%, with excellent dispersion stability. The traditional methods are prone to agglomeration due to uneven exfoliation, and need to reduce the concentration to maintain stability, resulting in low drying efficiency.

[0074] (Four) The graphene sample of Example 3 was detected by X-ray photoelectron spectroscopy (XPS) and an elemental analyzer for elemental composition: Carbon element purity verification: The content of carbon element detected by XPS is 99.3 at%, and the content detected by elemental analyzer is 99.5%, which is highly consistent with the original flake graphite (99.8 at%), and no additional impurity atoms are detected. Combined with the process of the present application (only using graphite, deionized water, PVP dispersant), the results prove that there is no chemical reagent residue outside the process, and the graphite carbon skeleton is not damaged due to chemical etching, oxidation and other reactions, and only physical force is used to realize interlayer dissociation.

[0075] Oxygen element source investigation: The content of oxygen element is only 0.6 at%, which is lower than the natural air adsorption amount (0.8-1.2 at%) of the original graphite in the conventional storage environment. Since no oxidizing reagent is involved in the present application, and the oxygen element in the PVP dispersant has been removed by vacuum drying, it can be determined that the trace oxygen is only the physical adsorption of air during sample storage, and there is no hydroxyl, carboxyl and other functional groups generated by chemical oxidation.

[0076] Hydrogen element residual traceability: the hydrogen element mass fraction is 0.3%, which is reduced to 0.1% after vacuum drying at 80°C for 2h (consistent with the original graphite hydrogen content). Combined with the process, it is known that the initial hydrogen element only comes from the deionized water for preparing the suspension, and no other hydrogen-containing chemicals (such as acid, alcohol reagent) are involved, and the residual amount is the same as the raw material after drying, which further confirms the cleanliness of the physical preparation.

[0077] Inorganic impurity control: the ash content of the sample is <0.01%, no metal (such as iron and stainless steel debris that may be generated by equipment wear) or inorganic salt impurities are detected, indicating that no external inorganic chemicals are introduced during the preparation process, and the equipment materials (such as ceramic inner liner and stainless steel pipeline) also do not contaminate the product.

[0078] In summary, the elemental composition characterization of the product of Example 3 directly proves that the elemental composition of the graphene sample is highly matched with the original graphite, without any chemical reagent residue, without the generation of new functional groups, and the carbon skeleton is complete, completely consistent with the characteristics of the product of pure physical exfoliation, fully proving that the method of the present application is a pure physical exfoliation process.

[0079] The above is only a preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing graphene using ultra-high pressure impinging flow through efficient physical exfoliation, characterized in that, Includes the following steps: The raw graphite blocks are crushed to a particle size of less than 100 μm to obtain a pretreated material; The pretreated material was mixed with a dispersant and a solvent to obtain a graphite suspension; The graphite suspension is pressurized to 250-300 MPa and ejected at high speed from multiple nozzles in the impact chamber for collision to obtain a graphene mixture; among the multiple nozzles, the included angle between the nozzle axes of adjacent nozzles is 130°-155°, the distance between adjacent nozzles is 1.8-2.2 cm, and the inner diameter of the impact chamber is 15-20 cm. The graphene mixture is filtered to obtain filter residue and filtrate containing graphene. The filtrate is dried to obtain the graphene product.

2. The method for preparing graphene using ultra-high pressure impinging flow through efficient physical exfoliation according to claim 1, characterized in that, The solvent is one of water, ethanol, and liquid carbon dioxide.

3. The method for preparing graphene using ultra-high pressure impinging flow through efficient physical exfoliation according to claim 2, characterized in that, Before mixing the pretreatment material with the dispersant and solvent, the method further includes: subjecting the pretreatment material to microwave expansion treatment.

4. The method for preparing graphene using ultra-high pressure impinging flow through efficient physical exfoliation according to claim 1, characterized in that, The concentration of the graphite suspension is 1~5wt%.

5. The method for preparing graphene using ultra-high pressure impinging flow through efficient physical exfoliation according to claim 1, characterized in that, When pressurizing the graphite suspension to 250~300MPa, a high-pressure plunger pump is used as the pressurizing device.

6. The method for preparing graphene using ultra-high pressure impinging flow through efficient physical exfoliation according to claim 1, characterized in that, After obtaining the graphene mixture, the following steps are also included: Monitor the values ​​of graphene particle size D50 and D90 in the graphene mixture: if D50 < 2 μm and D90 < 5 μm, filter the graphene mixture. If D50 > 2 μm or D90 > 5 μm, the graphene mixture will continue to be ejected at high speed through the nozzle for collision.

7. The method for preparing graphene using ultra-high pressure impinging flow through efficient physical exfoliation according to claim 1, characterized in that, When filtering the graphene mixture, a centrifuge or a filter plate machine is used.

8. The method for preparing graphene using ultra-high pressure impinging flow through efficient physical exfoliation according to claim 1, characterized in that, After obtaining the filter residue and the filtrate containing graphene, the process further includes: adding the filter residue into the graphite suspension.

9. The method for preparing graphene using ultra-high pressure impinging flow through efficient physical exfoliation according to claim 1, characterized in that, After obtaining the graphene mixture, the following steps are also included: The graphene mixture is returned to the graphite suspension and repeated 3 to 8 times.

10. The method for preparing graphene using ultra-high pressure impinging flow through efficient physical exfoliation according to claim 1, characterized in that, The drying process employs one of the following methods: spray drying, supercritical drying, or microwave vacuum drying.